The significance of traumatic haematoma in the region of the basal ganglia. - Macpherson, P (1986)
Computed tomography demonstrated a haematoma in the region of the basal ganglia in 61 of 2000 head injured patients. In 41 the haematoma occurred as an isolated lesion while in 20 there was another associated intracranial haematoma. Clinical and radiological differences within these groups are discussed. The patients with basal ganglia haematoma were more severely injured than those in a group who had an intracranial haematoma evacuated by craniotomy and the findings closely resembled those of a group of patients who had sustained diffuse brain damage. They share many features with those of patients with diffuse white matter injury and have a worse prognosis than other traumatic intracranial haematomas.